Uses, Motives, Functions, and Virtues of Silence in Argumentation in Light of Jadal and Ādāb al-Baḥth wa al-Munāẓarah - Taiai, Maria; Oruç, Rahmi (Afkar: Jurnal Akidah dan Pemikiran Islam, 2021)
Munāẓarah procedure determines who has the right to speak and who should remain silent until his turn comes. In fact, proper argumentation requires each party to remain silent where the right to speak is not theirs. However, the argumentation process in practice does not always follow the ideal rules of behaviour. One such instance is verbal aggressiveness, which often leads to anger and rapid information exchange with the offender. Such verbal exchange is generally characterized by an increase in volume and speed of speech, which usually lay the ground for a quarrel. The transition from healthy argumentation to quarrel is problematic because it changes the priorities of the parties involved in the verbal exchange from disclosing the truth to attacking the opponent. Then, the arguers are faced with the following question: What should I do when argumentation seems to be shifting to quarrel? Should I speak, or should I remain silent? The study argues the use of silence as an argumentation strategy prevents healthy argumentation from turning into a quarrel and enables discussants to conduct an ideal argumentation based on ethical standards. It does this in light of the disciplines of Jadal and Ādāb al-Baḥth wa al-Munāẓarah. The study first explains how munāẓarah procedure determines who has the right to speak and who should remain silent. Second, it discusses three argumentative moves in response to which silence might work better as an argumentative strategy. After that, it explores the intricate relationship between silence and tawfīq (divine aid). Finally, it investigates the relationship between silence - as a response to verbal aggressiveness - and the virtue of ḥilm (judiciousness).